2013
DOI: 10.1371/journal.pone.0062550
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Breast Cancer Susceptibility Locus at 4q31.22 Using a Genome-Wide Association Study Paradigm

Abstract: More than 40 single nucleotide polymorphisms (SNPs) for breast cancer susceptibility were identified by genome-wide association studies (GWASs). However, additional SNPs likely contribute to breast cancer susceptibility and overall genetic risk, prompting this investigation for additional variants. Six putative breast cancer susceptibility SNPs identified in a two-stage GWAS that we reported earlier were replicated in a follow-up stage 3 study using an independent set of breast cancer cases and controls from C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 43 publications
2
15
1
Order By: Relevance
“…GWAS also revealed many genomic loci associated with increased risk for breast [58][59][60][61][62], colorectal [63][64][65], cervical [66], lung [67][68][69], ovarian [70] and prostate [71,72] cancers, but no such association with increased cancer risk was detected on chromosome 1p36 (Table 3). Taken together, these results indicate that although some RUNX3 polymorphic markers may be associated with H. pylori-induced gastric changes, possibly due to an altered RUNX3 function in the infiltrating inflammatory immune cells, the absence of RUNX3 mutations in cancer and the lack of any association of RUNX3 with increased cancer risk do not support the RUNX3-TSG paradigm.…”
Section: Cancer Mutations and Genome-wide Association Studies (Gwas) mentioning
confidence: 99%
“…GWAS also revealed many genomic loci associated with increased risk for breast [58][59][60][61][62], colorectal [63][64][65], cervical [66], lung [67][68][69], ovarian [70] and prostate [71,72] cancers, but no such association with increased cancer risk was detected on chromosome 1p36 (Table 3). Taken together, these results indicate that although some RUNX3 polymorphic markers may be associated with H. pylori-induced gastric changes, possibly due to an altered RUNX3 function in the infiltrating inflammatory immune cells, the absence of RUNX3 mutations in cancer and the lack of any association of RUNX3 with increased cancer risk do not support the RUNX3-TSG paradigm.…”
Section: Cancer Mutations and Genome-wide Association Studies (Gwas) mentioning
confidence: 99%
“…Recently, a multi-stage association study conducted by us using a combined sample size of 7,219 breast cancer cases and healthy controls of Caucasian origin from Alberta, Canada, confirmed a potential prognostic value of SNP rs13280615 on chromosome 8q24.21 for breast cancer [Sehrawat et al, 2011;Sapkota et al, 2013c]. The SNP was for the first time shown to be of prognostic value with breast cancer outcomes (recurrence-free and overall survival) by independent investigators [Garcia-Closas et al, 2008].…”
Section: Common Variants For Breast Cancer Prognosismentioning
confidence: 87%
“…Such large studies have enriched the statistical power needed to capture common variants with much lower effect sizes and population frequencies. To date, GWASs conducted for breast cancer have identified more than 80 breast cancer susceptibility loci [Easton et al, 2007b;Hunter et al, 2007;Stacey et al, 2007Stacey et al, , 2008Gold et al, 2008;Ahmed et al, 2009;Thomas et al, 2009;Zheng et al, 2009;Gaudet et al, 2010;Long et al, 2010Long et al, , 2012Turnbull et al, 2010;Cai et al, 2011;Fletcher et al, 2011;Haiman et al, 2011;Sehrawat et al, 2011;Ghoussaini et al, 2012;Kim et al, 2012;Bojesen et al, 2013;Couch et al, 2013;French et al, 2013;Garcia-Closas et al, 2013;Michailidou et al, 2013;Sapkota et al, 2013c], and many more studies are underway. Motivated by the huge success of breast cancer GWAS, few studies have also been conducted to identify SNPs associated with breast cancer outcomes and other associated sub-phenotypes [Garcia-Closas et al, 2008;Azzato et al, 2010a, b;Shu et al, 2012;Rafiq et al, 2013].…”
mentioning
confidence: 99%
“…One SNP rs1429142 on Chr4q31.22, showed consistent associations in three independent cohorts for overall risk (Stages 1–3, p = 1.5 × 10 −7 adjusted for body mass index [BMI]; OR 1.28). Analysis based on menopausal status (Stages 1–3) revealed that SNP rs1429142 had an elevated risk for breast cancer among premenopausal women . (BMI adjusted p ‐value of 6.22 × 10 −10 and OR per‐allele of 1.49) compared to postmenopausal women (BMI adjusted p ‐value of 7.79 × 10 −03 and OR per‐allele of 1.17) with a p ‐value of heterogeneity ( p ‐het) <10 −03 .…”
Section: Introductionmentioning
confidence: 99%